2022
DOI: 10.3389/dyst.2022.10691
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interactions Between Cerebellar Dysfunction and Sleep Disturbances in Dystonia

Abstract: Dystonia is the third most common movement disorder. It causes debilitating twisting postures that are accompanied by repetitive and sometimes intermittent co- or over-contractions of agonist and antagonist muscles. Historically diagnosed as a basal ganglia disorder, dystonia is increasingly considered a network disorder involving various brain regions including the cerebellum. In certain etiologies of dystonia, aberrant motor activity is generated in the cerebellum and the abnormal signals then propagate thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 148 publications
2
25
0
Order By: Relevance
“…Given the cerebellums’ known projections to/from a variety of cortical regions involved not only in sleep regulation, but also regulation of specific sleep stages (NREM and REM) 49,50,56 , it was not unsurprising to find that sleep-stage specific deficits exist in both Pdx1 Cre ;Vglut2 fx/fx and Ptf1a Cre ;Vglut2 fx/fx mice. Other groups have found that dystonia patients 23,26 and mouse models of motor dysfunction 57 present with sleep-stage specific deficits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the cerebellums’ known projections to/from a variety of cortical regions involved not only in sleep regulation, but also regulation of specific sleep stages (NREM and REM) 49,50,56 , it was not unsurprising to find that sleep-stage specific deficits exist in both Pdx1 Cre ;Vglut2 fx/fx and Ptf1a Cre ;Vglut2 fx/fx mice. Other groups have found that dystonia patients 23,26 and mouse models of motor dysfunction 57 present with sleep-stage specific deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our in situ hybridization results (Figure 2 figure supplement 1), this may indicate that while the cerebellum is involved in the regulation of sleep, its role in circadian timekeeping is limited, at least in the current context. Indeed, while numerous projections exist between the cerebellum and the major circadian centers of the brain, including the hypothalamus, locus coeruleus, and pedunculopontine nucleus, direct projections between the cerebellum and the SCN master clock are lacking 49,50 . It is possible then that cerebellar access to circadian processes is tightly regulated and restricted to sleep rather than overall activity rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,49,50 Consistently, the cerebellum has sleep-related activity patterns, and its output neurons, which express clock genes, are connected with the wake-sleep brain network. 12,49 Alternatively, non-motor manifestations could be the consequence of other brain dysfunctions considering the wide expression of PRRT2 in the brain. 51 Paroxysmal disorders, such as PKD, are often seen as more "benign" compared with continuous movement disorders.…”
Section: Discussionmentioning
confidence: 96%